Skin Immune Landscape: Inside and Outside the Organism - Florence Abdallah; Lily Mijouin; Chantal Pichon (Mediators of Inflammation)
The skin is an essential organ to the human body protecting it from external aggressions and pathogens. Over the years, the skin was proven to have a crucial immunological role, not only being a passive protective barrier but a network of effector cells and molecular mediators that constitute a highly sophisticated compound known as the “skin immune system” (SIS). Studies of skin immune sentinels provided essential insights of a complex and dynamic immunity, which was achieved through interaction between the external and internal cutaneous compartments. In fact, the skin surface is cohabited by microorganisms recognized as skin microbiota that live in complete harmony with the immune sentinels and contribute to the epithelial barrier reinforcement. However, under stress, the symbiotic relationship changes into a dysbiotic one resulting in skin disorders. Hence, the skin microbiota may have either positive or negative influence on the immune system. This review aims at providing basic background information on the cutaneous immune system from major cellular and molecular players and the impact of its microbiota on the well-coordinated immune responses in host defense.